Living arrangement of Filipino older adults co-residing with single-parent offspring - Cruz, Isis Jen Y.; Maroon, Giana Denise L.; Reyes, Clarissa F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This is a qualitative study focused on the living arrangement of Filipino Older Adults co-residing with their single-parent offspring OACSPO. The study aimed to describe the living arrangement and the flow of support between the OACSPO and their single-parent offspring and determine the benefits and costs of their co-residential situation. A total of 20 OACSPOs and 16 single-parent offsprings from different household sizes and socioeconomic backgrounds from the National Capital Region were interviewed. The results of the study showed that as the household size increases, household economic status tends to decrease. The study also concluded that the most common type of flow of support between the OACSPO and the single-parent offspring is bidirectional. The most common type of support provided to the single-parent offspring are (1) monetary assistance and (2) educational support (for the single-parent offsprings child), while (1) monetary assistance and (2) helping with household chores and management are the commonly provided support to the OACSPO. The study also revealed that the most reported benefits received by the OACSPOs are (1) caregiving and companionship, (2) healthcare, and (3) socioemotional support in terms of joy and entertainment brought about by family members. As for the single-parent offsprings, (1) childcare, (2) monetary assistance, and (3) guidance and moral support are the most common types of benefits they receive. On the costs, majority of the OACSPO and the single-parent offsprings did not indicate any costs from their co-residential situation. Finally, the study revealed that majority of the OACSPO and the single-parent offsprings perceive that the OACSPO provide more support to the single-parent offsprings.
submitted June 2017
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Older people -- Dwellings -- Philippines; Older people -- Family relationships -- Philippines